DIAGNOSIS OF NON-VIRAL INFECTION IN FAOBROCHICKEN BREEDERS - AL – Sultan, I. I.; Shamun, A. A. (The Iraqi Journal of Veterinary Medicine, 2000)
This study indicate that the four lines of FAOBRO chicken breeders could be exposed to non-vira1 infections .The range of acceptability were variable from one line of breeders to another. The perccentage of yolk sac infection was ( 44. 3% ) at the age of first week in chickens in all lines. cocidial infection represent percentage ( 27.1% ) in the lines A,C and D only , cases of septicemia were recorded in brooding, rearing and eggs production with a percentage of (21.7%). the highest was seen in the eggs production period Air sacculitis occurrence was in a percentage of (3.5%) from the total cases examined and was seen in line B only at brooding period .Gout cases